Pengaruh Kebijakan Dividen, Kesempatan Investasi dan Profitabilitas terhadap Keputusan Investasi - Rahmiati, Rahmiati; Huda, Putri Nurul (Jurnal Kajian Manajemen Bisnis, 2015)
The purposes in this research are to examine the effect of dividend policy, investment opportunities, and profitability on investment decision of property and real estate in Indonesia stock exchange. The population is all property and real estate company registered in Indonesian stock exchange period 2009-2013. The result shows that: 1) The dividend policy has a negative significant affect on the investment decision of property and real estate in Indonesia stock exchange, 2) the investment opportunity has a positive significant affect on the investment decision of property and real estate in Indonesian stock exchange, 3) the profitability has a positive affect but not significant on the investment decision of property and real estate in Indonesia stock exchange.